Measuring the success of programmes of care for people living with dementia: a protocol for consensus building with consumers to develop a set of Core Outcome Measures for Improving Care (COM-IC) - Thomas Morris; Susan E Kurrle; Susanna Dodd; Paula Williamson; Leon Flicker; Len Gray; Osvaldo P Almeida; Tracy Comans; John Quinn; Kim Nguyen; Judy A Lowthian; Dominic Trépel; et al. (BMJ Open)
Introduction The Core Outcome Measures for Improving Care (COM-IC) project aims to deliver practical recommendations on the selection and implementation of a suite of core outcomes to measure the effectiveness of interventions for dementia care.Methods and analysis COM-IC embeds a participatory action approach to using the Alignment–Harmonisation–Results framework for measuring dementia care in Australia. Using this framework, suitable core outcome measures will be identified, analysed, implemented and audited. The methods for analysing each stage will be codesigned with stakeholders, through the conduit of a Stakeholder Reference Group including people living with dementia, formal and informal carers, aged care industry representatives, researchers, clinicians and policy actors. The codesigned evaluation methods consider two key factors: feasibility and acceptability. These considerations will be tested during a 6-month feasibility study embedded in aged care industry partner organisations.Ethics and dissemination COM-IC has received ethical approval from The University of Queensland (HREC 2021/HE001932). Results will be disseminated through networks established over the project, and in accordance with both the publication schedule and requests from the Stakeholder Reference Group. Full access to publications and reports will be made available through UQ eSpace (https://espace.library.uq.edu.au/), an open access repository hosted by The University of Queensland.